CREATIVE-PEDAGOGICAL APPROACH IN TEACHING THE DISCIPLINE “RADIATION TECHNOLOGIES” IN MEDICAL UNIVERSITIES (Conferencea, 2024)
As a rule, at the beginning of the lesson-lecture there is a repetition of the past topic. This can be done with the help of a “Blitz survey” in which the teacher asks questions about the past topic, and students should answer them briefly, clearly and clearly in a short period of time. Thus, there is also a parallel warm-up of memory, that is, students have the skills to recall the past, remember the present, and apply all this valuable and useful information in the future.To clarify the new topic “Radionuclide diagnostics”, you can use the “Tree of Knowledge”, where questions are asked on the reverse sides of the leaves of this tree, which students answer immediately, without leaving the blackboard, without hesitation. For example, these may be questions: “The discovery of which rays gave a powerful impetus to the use of physics in medicine?”, “What do you know about ionizing radiation?”, “Explain the essence of the laws of incidence, refraction and reflection of rays?”, etc.